PENGELOLAAN LIMBAH PERTANIAN BERBASIS TEKNOLOGI KOMPOS SEBAGAI SOLUSI MASALAH LINGKUNGAN DI DESA KELORARUM LAMONGAN - Kusumawati, Dian Eka; Istiqomah, Istiqomah; Setiawan, Agus; Achmad, Shihabuddin; Nandra, Cinta Salsa Quen (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
Waste problems are a problem experienced by various regions, including Kelorarum Village, Tikung District, Lamongan Regency, especially agricultural waste which is still often not utilized properly. In addition, the agricultural sector in Kelorarum Village still relies on chemical fertilizers which will have an impact on reducing environmental sustainability. The purpose of this community service program is to reduce agricultural waste by processing it into organic fertilizer through training which will have an impact on increasing the knowledge and skills of partners in processing agricultural waste into organic fertilizer through the composting method with a composter. This community service program was carried out from June to August 2024 in Kelorarum Village, Tikung District, Lamongan Regency which was attended by the local village Farmer Group. This activity was carried out in several stages, namely observation, socialization, fertilizer making training and evaluation. The results of this activity showed a positive response from the training participants as seen from the enthusiasm in participating in this activity, in addition, the training participants (partners) experienced increased knowledge and skills in processing agricultural waste into organic fertilizer. This is evidenced by the success of the partners in making organic fertilizer. Through this activity, it can reduce agricultural waste around the partner’s environment and can produce organic fertilizer products that can be used by partners to meet fertilizer needs on their agricultural land and reduce the use of chemical fertilizers and can increase partner income.